End of the (Pipe)Line? Understanding how States Manage the Risks of Oil and Gas Wells. Issue 2 (29th January 2021) - Nelson, Steven; Fisk, Jonathan M.
Abstract: An understudied aspect of the "fracking" debate involves questions and challenges associated with abandoned wells and well closure. States regulators have a variety of options when it comes to policies and financial tools related to site closure and remediation including bonds, fees, and specific legacy funds. Those advocating more robust financial programs suggest that they are necessary to mitigate risks to the public. Opponents contend that they dissuade operators from investing in older fields and add costs that are passed on to consumers. Using a novel index of state financial tools, this paper assesses why some states adopt more robust financial assurance while others do not. Abstract : "水力压裂"辩论中研究不足的一个方面包括废弃井及油井关闭的相关疑问和挑战。就与场地关闭和包括履约保证、补偿费、特定遗产基金在内的补救措施相关的政策和财政工具而言，各州的监管者拥有一系列选择。那些倡导更稳健的财政计划的人士认为，这些计划对缓解公众面临的风险而言是必要的。反对者辩称，这些计划阻止经营者投资已使用过的油田，并增添了消费者的成本。通过使用一项关于各州财政工具的独特指标，本文评估了为何某些州比其他州采取了更为稳健的财政保障。 Abstract : Un aspecto poco estudiado del debate sobre el "fracking" implica preguntas y desafíos asociados con los pozos abandonados y el cierre de pozos. Los reguladores estatales tienen una variedad de opciones cuando se trata de políticas y herramientas financieras relacionadas con el cierre y remediación de sitios, incluidos bonos, tarifas y fondos heredados específicos. Quienes abogan por programas financieros más sólidos sugieren que son necesarios para mitigar los riesgos para el público. Los opositores sostienen que disuaden a los operadores de invertir en campos más antiguos y agregan costos que se transfieren a los consumidores. Utilizando un índice novedoso de herramientas financieras estatales, este documento evalúa por qué algunos estados adoptan una garantía financiera más sólida mientras que otros no.